Meta-Analysis of Postoperative Adjuvant Hepatic Artery Infusion Chemotherapy Versus Surgical Resection Alone for Hepatocellular Carcinoma - Ke, Qiao; Wang, Lei; Wu, Weimin; Huang, Xinhui; Li, Ling; Liu, Jingfeng; Guo, Wuhua (Frontiers in Oncology, 2021)
Background: To systematically identify the long-term efficacy of postoperative adjuvant hepatic artery infusion chemotherapy (HAIC) for the patients with hepatocellular carcinoma (HCC). Methods: PubMed, MedLine, Embase, the Cochrane Library, Web of Knowledge were searched to collect the eligible studies up to March 31st 2021 that compared the surgical resection (SR) versus SR+HAIC for HCC patients. The endpoints were overall survival (OS) rates and disease-free survival (DFS) rates, and the effect size were determined by hazard ratio (HR) with 95% confidence interval (CI) . Results: A total of 12studies (two RCTs and 10 Non-RCTs) including 1333 patients were eligible for this meta-analysis. The pooled results showed that OS and DFS rates in SR+HAIC group were both better than those in SR alone group(HR=0.56, 95%CI=0.41-0.77, P<0.001; HR=0.66,95%CI=0.55-0.78, P<0.001; respectively). Furthermore, subgroup analysis showed that patients would be benefited from SR+HAIC regardless of chemotherapy regimens and courses (all P<0.05), and patients with microvascular invasion (MVI) or macrovascualr invasion (MaVI) would also be benefited more from SR+HAIC in terms of OS and DFS (all P<0.05). Conclusion: Postoperative adjuvant HAIC could improve the long-term prognosis of HCC patients, especially for those with microvascular or macrovascular invasion, regardless of chemotherapy regimen and courses, but it deserves further validation.